Contributory parenting: A “priceless shift” from indirect to direct parenting - Madhuri Taranikanti; Archana Gaur; Vidya Ganji; Sai Shriya Taranikanti (Indian Journal of Community Medicine, 2023)
Parenting is a valuable investment that determines the quality of future independent life. From an evolutionary aspect, it has been well ingrained in the minds of humans as to how much resource each parent should contribute to this energy and time-consuming task. To encourage father's contribution towards parenting and reduce the stress on mother, the concept of paid paternal leave has been implemented. Mere presence of the father in terms of the quantity of time spent without much qualitative value has no benefit, but the assumption that fathers are less competent based on their lower performance might also not be acceptable. An intriguing finding has demonstrated that prolonged contact with the infant triggers a change in previously absent male parenting behavior. With incentives on one hand and associated societal stigma on the other hand, it is to be analyzed whether the purpose of true parenting by fathers is being achieved. Hence, in the concept of contributory parenting it is necessary to recognize and respect each parenting style with the ultimate benefit being passed on to the child.